-3x平方-4xy-6xy-(-y平方)-2x平方-3y平方求值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 22:06:08
-3x平方-4xy-6xy-(-y平方)-2x平方-3y平方求值-3x平方-4xy-6xy-(-y平方)-2x平方-3y平方求值-3x平方-4xy-6xy-(-y平方)-2x平方-3y平方求值-3x平
-3x平方-4xy-6xy-(-y平方)-2x平方-3y平方求值
-3x平方-4xy-6xy-(-y平方)-2x平方-3y平方求值
-3x平方-4xy-6xy-(-y平方)-2x平方-3y平方求值
-3x平方-4xy-6xy-(-y平方)-2x平方-3y平方
=-5x平方-2y平方-10xy
3x平方-5x平方y-{2x平方y+6xy平方-[2xy平方-3x平方y+(3x平方y-4xy平方】}
-3x平方-4xy-6xy-(-y平方)-2x平方-3y平方求值
(2xy平方+3xy平方)-(6x平方y-3xy平方)=
(2x平方y+3xy平方)-(6x平方y-3xy平方)等于多少
初一2x平方-5xy-3x平方+4y平方+3xy-y平方
计算:(x平方+y平方/xy-x平方/xy+y平方-y平方/x平方+xy)除以3/xy
(3x平方-4y平方)+[-(x平方-2xy-y平方)]-[(3x平方-2xy-y平方)]
分式计算6x平方-3xy+7y平方 分之3x平方-4xy+2y平方
化简:(6x的平方y+3xy的平方)-(-x的平方y-4xy的平方)
3(x平方y+xy)-4(xy-2x平方y)-(xy)
(2X平方y+3xy平方)-(6x平方-3XY平方)(计算)
-3(2x的平方y-xy)+4(x的平方+xy-6)=
计算 5xy的平方-【3xy的平方-(4xy的平方-2x的平方y)】+2x的平方y-xy的平方
已知x/y=3/4,那么x平方-y平方/x平方-2xy+y平方除以xy+y平方/x平方-xy
减去2-3x等于6x平方-3x-8的代数式是?已知x-y=3,xy=-4,x平方+y平方=?x平方+xy+y平方=?x平方-3xy+y平方=?
[6XY平方(X平方-3XY)-(-3X平方Y)三次方]/3X平方Y平方
x平方+4xy-4y平方
x平方-5xy+6y平方